Experience in laparoscopic cholecystectomy at the Hospital de Clínicas José de San Martín: Buenos Aires' University - Ferraina, Pedro A.; Diez, Julio A.; Merello Lardies, Jorge; Suárez Anzorena, Francisco; Sarotto, Luis E.; Horgan, Santiago; Tellias, Rosa (Cirugía del Uruguay, 1993)
In march 1991 a prospective study of laparoscopic cholecystectomy was started.